Proceedings of the 23rd IEEE International Symposium on Reliable Distributed Systems, 2004. 2004
DOI: 10.1109/reldis.2004.1353003
|View full text |Cite
|
Sign up to set email alerts
|

Token-based atomic broadcast using unreliable failure detectors

Abstract: Many atomic broadcast algorithms have been published in the last twenty years. Token-based algorithms represent a large class of these algorithms. Interestingly, all the token-based atomic broadcast algorithms rely on a group membership service, i.e., none of them uses unreliable failure detectors directly. The paper presents the first token-based atomic broadcast algorithm that uses an unreliable failure detector -the new failure detector denoted by R -instead of a group membership service. The failure detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 21 publications
(43 reference statements)
0
36
0
3
Order By: Relevance
“…A work close to ours is R. Ekwall et al's [21]: nodes are organized in a logical ring and the token is sent to the f + 1 successors, where f is the maximum number of failures. However, the goal of the authors' approach differs from ours.…”
Section: Monitor Nodes Predictable Nodesmentioning
confidence: 95%
“…A work close to ours is R. Ekwall et al's [21]: nodes are organized in a logical ring and the token is sent to the f + 1 successors, where f is the maximum number of failures. However, the goal of the authors' approach differs from ours.…”
Section: Monitor Nodes Predictable Nodesmentioning
confidence: 95%
“…We want a single token to "glue" the various instances of consensus together. A variation of the algorithm that follows is presented in [19]. The algorithm presented here is easier to understand, with processes that send regular messages (at line 10) and tokens (versus only tokens in [19]).…”
Section: Token Based Atomic Broadcast Using Unreliable Failure Detmentioning
confidence: 99%
“…The performance of the token based atomic broadcast algorithm presented above has been evaluated in simulation in [19]. This simulation showed that the performance of the new algorithm is better than previous algorithms using failure detectors.…”
Section: Experimental Performance Evaluationmentioning
confidence: 99%
See 2 more Smart Citations